Development, processing and applications of bio-sourced cellulose nanocrystal composites. (April 2020) - Calvino, Céline; Macke, Nicholas; Kato, Ryo; Rowan, Stuart J.
Graphical abstract: The incorporation of cellulose nanocrystals into bio-based materials represents a promising approach to sustainable nanocomposites. This review summarizes the current state of the art in the field and highlights the different strategies employed to process reinforced bio-based nanocomposites, including pre-treatment of the CNCs, the use of additives, such as surfactants or plasticizers, as well as covalent modification of the CNC surface. The additional benefits of the use of CNCs to prepare bio-based materials with new functionalities, as well as their potential future applications in a variety of fields are discussed. Abstract: Plastic pollution concerns have catalyzed research into green materials with the specific goal of accessing new bio-derived and bio-degradable polymers with improved property profiles. One way to achieve these new materials is through the incorporation of nanofillers into bio-based polymer matrices. Cellulose nanocrystals (CNCs), which are extracted from biomass, have been investigated as one route to bio-based composites with enhanced performance. The combination of the excellent reinforcement capabilities of these bio-derived, nanosized particles along with relatively low production cost and biodegradability makes cellulose-based nanocomposites an attractive and promising approach to the next generation of green materials. Discussed herein is an overview of the use of CNCs to access reinforced bio-based nanocomposites, with particular focus on bio-available polyester and polysaccharide matrices. The characteristic changes provided by the incorporation of the nanofillers into the bio-based materials and their advantages and drawbacks are discussed. Specifically, the different parameters influencing mechanical reinforcement and barrier properties, such as the nature of processing, use of additives or CNC surface modifications are reviewed. Finally, the benefits of using CNC fillers in a number of potential future application areas, including polymer compatibilization, water purification, biomedical and electronics are outlined.